Pengaruh Literasi Keuangan, Inklusi Keuangan dan Financial Technology terhadap Perilaku Keuangan dengan Lifestyle Sebagai Variabel Pemoderasi: (Studi pada Mahasiswa Generasi Z di Universitas Prof. Dr. Hazairin, SH) - Rahmad Ramadhani; Sintia Safrianti; Fauzan Fauzan (Lembaga Pengembangan Kinerja Dosen, 2025)
In the current era of globalization, there are many changes in financial behavior, therefore financial intelligence is absolutely necessary for a student. Because, financial intelligence includes how a person manages their finances well, including expenses, investments, savings, and other financial aspects. This study aims to determine how much influence financial literacy, financial inclusion, and Financial Technology have on financial behavior and to determine how much Lifestyle moderates it in generation Z students at Prof. Dr. Hazairin SH University. This research method is quantitative by distributing questionnaires to 160 students in generation Z at Prof. Dr. Hazairin SH University. Sampling techniques that use non-probability sampling techniques.. Data analysis was carried out using the Partial Least Square - Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS 4 software. The results of the analysis show that partially Financial Technology, Financial Literacy and Lifestyle have a positive and significant effect on Financial Behavior. Conversely, Financial Inclusion does not have a positive and significant effect on Financial Behavior. And Lifestyle as a moderating variable shows a significant influence in strengthening the relationship between Financial Inclusion and Financial Behavior. Meanwhile, Lifestyle as a moderating variable does not show a significant influence in strengthening the relationship between Financial Literacy and Financial Technology.